Profil Kesiapan dan Pemahaman Guru Biologi terhadap Pelaksanaan Asesmen Psikomotorik dan Afektif Selama Pembelajaran Online di SMA Seluruh Kecamatan Comal, Pemalang - Eka Nunik Suharjanti; Ipah Budi Minarti; Lussana Rossita Dewi (Florea : Jurnal Biologi dan Pembelajarannya, 2021)
Assessment is part of a teacher's pedagogic competence and curriculum-13 must carry out cognitive, psychomotor and affective assessments. Online learning causes the implementation of psychomotor and affective assessments to be hampered. This study aims to determine the readiness and understanding of Biology teachers on psychomotor and affective assessments during online learning. The method used is qualitative with descriptive analysis. The sampling technique is a saturated sampling technique. The subject of the study, namely the Biology teacher of the SMA in Comal District, opened 5 teachers through filling out questionnaires distributed online on google forms and RPP documentation as well as evidence of the implementation of the assessment, while the student questionnaires were used as secondary data. Data analysis using descriptive analysis consists of reduction, data display, and verification. This study resulted in the finding that the teacher's assessment readiness profile during online learning can be declared ready to carry out psychomotor and affective assessments. Meanwhile, the profile of teachers' understanding of psychomotor and affective assessments can generally be obtained at a low level. An understanding profile that has an impact on misconceptions in the realm of assessment and the development of an assessment rubric that is not yet good so that human application cannot run optimally. In addition, the application of psychomotor and affective assessments during online learning is influenced by the factors of the teacher's IT ability and the facilities owned by the students.